COMPARATIVE ANALYSIS OF GPON AND XGSPON TECHNOLOGY IN THE DESIGN OF FIBER ACCESS NETWORKS IN GREENWOOD HOUSING SEMARANG - Yohandri Natan; Sukiswo Sukiswo; Teguh Prakoso (Universitas Diponegoro, 2019)
The demand of telecommunication services will have increment in quantity and quality.The needs of customer ,which is becoming more complex, is one of the reason for technology development. One of the technologies that can fulfil these needs is Gigabit-capable Passive Optical Network (GPON) and X-Gigabit-capable Simetrical Passive Optical Network (XGSPON) in Fiber-to-The-Home services (FTTH). Based on ITU-T recommendation G.984, GPON has 2,5 Gbps downstream bitrate and 1,25 Gbps upstream bitrate. On the other hand, according to ITU-T recommendation G.9807, XGSPON has 10 Gbps for both upstream and downstream bitrate. FTTH planning is important. FTTH network can be planned for aerial system or duct system. After the network planning is finished, the simulation is needed to ensure the plan fulfils the standards. This simulation is performed by Optisystem 7.0. The parameters for determining the network QoS are rise time budget, rise time budget, q-factor, and BER. These parameters based on ITU-T recommendations and PT. Telekomunikasi Indonesia’s standard. The result shows that the network plan for both aerial and duct system, in each technology has fulfilled the requirements and can be implemented.